Genomic screening and molecular dynamics simulations of cyanovirin‐N homologs from cyanobacteria phylum. Issue 3 (29th October 2020) - Siqueira, Andrei Santos; Lima, Alex Ranieri Jerônimo; Aguiar, Delia Cristina Figueira; Santos, Alberdan Silva; Gonçalves, Evonnildo Costa
Abstract: The phylum cyanobacteria are one of the most ancient groups of organisms on the planet and are well recognized due to its wide distribution, ecological role, and biotechnological potential. Cyanobacterial lectins are being extensively explored due to their antiviral activity, mainly because of their capacity of inhibiting HIV strains from infecting human cells by gp120 and gp41 binding. Cianovirin‐N from Nostoc ellipsosporum was the first lectin isolated with this property. Since then, various homologs have been discovered and characterized. In this article, we present results of a genomic screening to find cyanovirin‐N homologs (CVNH) in all cyanobacteria genomes available in the GenBank, resulting in 155 CVNH proteins with 63 presenting significant identity differences of cyanovirin‐N. Homology modeling and molecular dynamics were employed to characterize 18 unexplored models and their functional capacity of binding to Manα(1‐2)Man. Results presented here support the hypothesis of multiple ligand recognition for the CVNH family and may help to understand the function of these lectins for the producer cyanobacteria. Additionally, the theoretical results observed here justify carrying out experimental investigations that can expand the therapeutic potential of cyanobacterial lectins.